2014
DOI: 10.3329/bjvm.v11i1.17728
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tulsi leaves and neem leaves extract in broiler production

Abstract: The efficacy of tulsi (Ocimum sactum) and neem (Azadirachta indica) leaves extract as a growth promoter were studied in broiler. A total of 40 day-old broiler chicks were purchased from Kazi hatchery and after three days of acclimatization the chicks were randomly divided into four groups (n=10). No vaccination schedule was practiced and no antibiotic was added in ration of group A, B, C, and D respectively. Group A served control without any supplements while group B, C and D were supplemented with combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…Similarly, effect of tulsi leaf extract as a growth promoter on broiler production also studied by Hasan et al, 2016, and found significant increase of live weight. Tulsi with neem and other herbs as a growth promoter are found to have greater feed conversion efficiency in broilers (Nath et al, 2012;Khatun et al, 2013) which are in line with the present study. In a separate study, Siddig and Abdelati (2001) found higher weight gain in broilers in ration containing seeds of Nigella sativa and vitamin A.…”
Section: Study Of Ntg Extract On Hematological Parameter Of Broilerssupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, effect of tulsi leaf extract as a growth promoter on broiler production also studied by Hasan et al, 2016, and found significant increase of live weight. Tulsi with neem and other herbs as a growth promoter are found to have greater feed conversion efficiency in broilers (Nath et al, 2012;Khatun et al, 2013) which are in line with the present study. In a separate study, Siddig and Abdelati (2001) found higher weight gain in broilers in ration containing seeds of Nigella sativa and vitamin A.…”
Section: Study Of Ntg Extract On Hematological Parameter Of Broilerssupporting
confidence: 91%
“…Extracts of different medicinal plant as a natural antimicrobials have been studied in recent years (Hsieh and Mau, 2001). Tulsi and neem extract in broiler production as a herbal growth promoter is found economic and safe (Khatun et al, 2013;Prasannabalaji et al, 2012). But there is no published report on effeicacy of three natural herbs (tulsi and neem leaves, and ginger ) in broiler production is found in literature.…”
Section: Issn: 2319-7706 Volume 9 Number 3 (2020)mentioning
confidence: 99%
“…Better feed conversion ratio of the broiler using rations supplemented with papaya leaf and kalo jeera seeds leave extract may be attributed to the antibacterial properties of these supplements, which resulted in better absorption of the nutrients present in the gut and finely leading to improvement in feed conversion ratio of the rations (Khatun et al, 2013). This study has revealed that papaya leaf and kalo jeera seeds extract had no significant effect on the hematological parameters (Table 4).…”
Section: Resultsmentioning
confidence: 80%
“…After washing, the fresh leaves were cut into small pieces by simple scissors and dried in oven and 20gm mixed with added water made up to 1 litter. Then boiled it made up to 1 liter and stored in a refrigerator at 4°C to preserve the active ingredients of juice (Khatun et al, 2013). After 7 days all the 40 broiler chicks were randomly divided into 2 groups A (n=20) and B (n=20).…”
Section: Methodsmentioning
confidence: 99%